انعكاسات جائحة كورونا على إدارة المؤسسات الرياضية دراسة ميدانية للجمعيات الرياضية بولاية المسيلة - رداوي, رضوان; هبوب, حمزة; د.بوصلاح, النذير (My University, 2021)
تهدف الدراسة الى معرفة انعكاسات جائحة كورونا على إدارة المؤسسات الرياضية، والتعرف على مختلف الأثار المترتبة على إدارة المؤسسات الرياضية جرَاء الأزمة الصحية العالمية، والوقوق على الصعوبات والتحديات التي واجهتها لتجاوز الأزمة، حيث استخدمنا المنهج الوصفي في الدراسة، وتضمَنت العينة (40) رئيس جمعية رياضية، وقد تم إعداد استمارة استبيان لجمع البيانات، وتحليلها من خلال برنامج التحليل الإحصائي (SPSS)،أظهرت النتائج ان لجائحة كورونا انعكاسات على إدارة المؤسسات الرياضية من الناحية الاقتصادية ومن الناحية الاجتماعية ومن الناحية الصحية والنفسية ومن أهم التدابير والاقتراحات الواجب اتخاذه مستقبلا ما يلي: - تخصيص اعتمادات مالية كافية لمواجهة الأزمات المختلفة. - البحث عن صيغ جديدة لتنويع موارد المؤسسات الرياضية. - مراجعة المساعدات الممنوحة من طرف الدولة في ظل الأزمات. - ضرورة تخصيص وتوظيف أخصائيين نفسانيين واجتماعيين من اجل التكفل بالحالات النفسية والاجتماعية المختلفة بين المستخدمين داخل المؤسسات الرياضية. - مواكبة التطورات التكنولوجية كبدائل لتسير المؤسسات الرياضية في ظل الأزمات والعمل عن بعد. - إقامة دورات تدريبية لتطوير قدرات ومهارات المستخدمين للتحكم الجيد في التكنولوجيات الحديثة. الكلمات المفتاحية: جائحة كورونا- المؤسسات الرياضية- الأزمات Study summary: The study aims to know the repercussions of the Corona pandemic on the management of sports institutions, to identify the various effects of the management of sports institutions as a result of the global health crisis, and to face the difficulties and challenges it faced to overcome the crisis, as we used the descriptive approach in the study, and the sample included 40 presidents of sports associations. A questionnaire was prepared to collect data, and analyze it through the Statistical Analysis Program (SPSS). The results showed that the Corona pandemic has repercussions on the management of sports institutions in terms of economic, social, health and psychological aspects. Among the most important measures and suggestions to be taken in the future are the following: - Allocating sufficient funds to face various crises. - Searching for new formulas to diversify the resources of sports institutions. - Review the aid granted by the state in light of crises. - The need to allocate and employ psychologists and social anthropologists in order to take care of different psychological and social situations among users within sports institutions. - Keeping abreast of technological developments as alternatives for sports institutions to run in light of crises and remote work. - Holding training courses to develop the capabilities and skills of users for good control of modern technologies
Keywords: جائحة كورونا; المؤسسة الرياضية; الازمات